Scalable Learning Of Collective Behaviour - MD Anwar Ali , MD khaliq, Ahmed ullah khan (International Journal of Scientific Research and Management (IJSRM), 2017)
In a multimode consists of heterogeneous types of actors among which various types of interactions between them In a multimode, both actor membership and interactions evolve, which causes a problem for identifying the evoving communites. Identifying communites can help understanding the structural properties of the network,address the data shortage, unbalanced problems and tasks lik targeting marketing and finding within or between groups. In a proposed system to address the issue by employing temporal information to anayze a multimode network an scalability issue are carefully studied.